Optimalisasi Panduan Pelaksanaan Kebersihan, Kesehatan, Keselamatan, Dan Kelestarian Lingkungan Di Taman Hutan Raya Ir. H. Djuanda Pasca Revitalisasi - I Dewa Ayu Dewi Prasanti; I Wayan Kiki Sanjaya; Kadek Ayu Ekasani (Journal of Innovative and Creativity, 2025)
This research focuses on implementing Standard Operating Procedures (SOP) in the Ir. H. Djuanda Grand Forest Park (Tahura) in Bandung, West Java. As a conservation area, Tahura Ir. H. Djuanda is renowned for its natural beauty, biodiversity, and significant historical value. However, tourism management in this area faces several challenges, including limited infrastructure, accident risks, and suboptimal management of tourist attractions, which fall short of theoretical and management expectations. The urgency of this research stems from the lack of clearly identified SOPs for tourism management in the park, particularly regarding cleanliness, health, safety, and environmental sustainability (CHSE). This study is guided by two main research questions: (1) How were the guidelines for cleanliness, health, safety, and environmental sustainability implemented in Tahura Ir. H. Djuanda before revitalization? (2) What strategies and recommendations, aligned with SNI 9042-2021, are appropriate for optimizing these guidelines after the revitalization process?. The research aims to evaluate the application of cleanliness, health, safety, and environmental sustainability practices in Tahura Ir. H. Djuanda before revitalization and to formulate recommendations for post-revitalization optimization based on SNI 9042-2021. Additionally, the study identifies the strengths, weaknesses, opportunities, and threats (SWOT) in the area's management. A qualitative approach was employed, utilizing a literature review, field observations, and in-depth interviews with park management and stakeholders. The analysis reveals that SOP implementation was not standardized before revitalization and remained fragmented, failing to comprehensively ensure cleanliness, health, safety, and environmental sustainability. Based on SNI 9042-2021, the study recommends optimizing SOPs through the development of standardized documentation, capacity building for human resources, infrastructure improvements, and strengthening monitoring and evaluation systems. The implications of this research are expected to serve as a reference for park management in achieving sustainable tourism management that meets national standards.